The neural stem cell properties of Pkd2l1+ cerebrospinal fluid-contacting neurons in vivo - Cao, Liang; Huang, Ming-Zhi; Zhang, Qiang; Luo, Zhang-Rong; Zhang, Yi; An, Ping-Jiang; Yang, Lei-Luo; Tan, Wei; Wang, Chun-Qing; Dou, Xiao-Wei; Li, Qing (Frontiers in Cellular Neuroscience, 2022)
The neural stem cells in the ventricular-subventricular zone of the adult mammalian spinal cord may be of great beneﬁt for repairing spinal cord injuries. However, the sources of neural stem cells remain unclear. Previously, we have confirmed that cerebrospinal fluid-contacting neurons (CSF-cNs) have neural stem cell potential in vitro. In this study, we verified the neural stem cell properties of CSF-cNs in vivo. In mouse spinal cords, PKD2L1+ CSF-cNs localized around the central canal express neural stem cell markers. In vitro, PKD2L1+ CSF-cNs form a neurosphere and express neural stem cell markers. Activation and proliferation of CSF-cNs can be induced by injection of the neurotrophic factors bFGF and VEGF into the lateral ventricle. Spinal cord injury also induces neural stem cell activation and proliferation of CSF-cNs. Collectively, our results demonstrate that PKD2L1+ CSF-cNs have neural stem cell properties in vivo and may be involved in spinal cord injury recovery.